MODERN TECHNOLOGIES OF EDUCATION OF ETHNO-CULTURAL TOLERANCE IN YOUTH STUDENTS: THEORETICAL ASPECT - Tangirov Eldor Sayfullayevich (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
The national demographic map of modern Uzbekistan is characterized by multi-ethnicity. Therefore, the processes of interethnic interaction that take place in the state give rise to new socio-cultural and pedagogical problems. One of these problems – the formation of a new generation of citizens of Uzbekistan, worthy successors to the tradition of previous generations, successors to the spiritual culture of their people, able to coexist and communicate without conflict with representatives of other ethnic populations, while maintaining national identity in conditions of compact living in a multinational educational and cultural space. So, we are talking about instilling ethnic tolerance in the younger generation.